2013
DOI: 10.1186/1472-6750-13-43
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the efficiency of generating genetically engineered pigs by nuclear transfer: multi-factorial analysis of a large data set

Abstract: BackgroundSomatic cell nuclear transfer (SCNT) using genetically engineered donor cells is currently the most widely used strategy to generate tailored pig models for biomedical research. Although this approach facilitates a similar spectrum of genetic modifications as in rodent models, the outcome in terms of live cloned piglets is quite variable. In this study, we aimed at a comprehensive analysis of environmental and experimental factors that are substantially influencing the efficiency of generating geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 70 publications
2
59
3
Order By: Relevance
“…Here, we obtained six offspring: two (33.3%) were stillborn and three (50%) died within 24 hr after birth. Our stillbirth percentage was similar to the findings of a large‐scale study using more than 300 cloned piglets, which found that 24% were stillborn and 31% died soon after birth (Kurome et al, ). In this study, the piglets that died within 24 hr after birth weighed less at birth than wild‐type piglets.…”
Section: Discussionsupporting
confidence: 89%
“…Here, we obtained six offspring: two (33.3%) were stillborn and three (50%) died within 24 hr after birth. Our stillbirth percentage was similar to the findings of a large‐scale study using more than 300 cloned piglets, which found that 24% were stillborn and 31% died soon after birth (Kurome et al, ). In this study, the piglets that died within 24 hr after birth weighed less at birth than wild‐type piglets.…”
Section: Discussionsupporting
confidence: 89%
“…Lived clones obtained from adult somatic cells in sheep [31], [32], cattle [33]-[36], and pigs [37]-[40] have also been reported. Kurome et al indicated that there was no significant difference for the effects of different donor cell sources on cloning success [41]. In the present study, we used fibroblast cells isolated from ear tissue of the two-month-old dairy goat as donor cells for SCNT.…”
Section: Discussionmentioning
confidence: 95%
“…In the pig the situation is intermediate and no dramatic phenotypes are reported (Kurome et al, 2013). The low efficiency is compensated by the transfer of many cloned embryos per recipients to ensure a high pregnancy rate and a reasonable number of newborn piglets.…”
Section: The Stem Cells and Somatic Cell Nuclear Transfermentioning
confidence: 99%